Triboelectric Nanogenerator Devices: Triboelectric Nanogenerator Accelerates Highly Efficient Nonviral Direct Conversion and In Vivo Reprogramming of Fibroblasts to Functional Neuronal Cells (Adv. Mater. 34/2016). Issue 34 (September 2016) - Jin, Yoonhee; Seo, Jungmok; Lee, Jung Seung; Shin, Sera; Park, Hyun‐Ji; Min, Sungjin; Cheong, Eunji; Lee, Taeyoon; Cho, Seung‐Woo
Abstract : On page 7365, T. Lee, S.‐W. Cho, and co‐workers report a novel platform based on a triboelectric nanogenerator to enhance the direct generation of induced neuronal cells from skin fibroblasts through the nonviral gene delivery of neuronal lineage‐specific transcription factor genes, both in vitro and in vivo. The triboelectric nanogenerator can be an effective platform for reprogramming cells for the production of functional neuronal cells for therapeutic applications.